2018
DOI: 10.1371/journal.pntd.0006935
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling of the effect of rainfall flushing on dengue transmission in Singapore

Abstract: BackgroundRainfall patterns are one of the main drivers of dengue transmission as mosquitoes require standing water to reproduce. However, excess rainfall can be disruptive to the Aedes reproductive cycle by “flushing out” aquatic stages from breeding sites. We developed models to predict the occurrence of such “flushing” events from rainfall data and to evaluate the effect of flushing on dengue outbreak risk in Singapore between 2000 and 2016.MethodsWe used machine learning and regression models to predict da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 80 publications
4
77
1
4
Order By: Relevance
“…Also, stagnant water and poor sanitary and hygiene practices may make suitable breeding sites for the mosquitoes. In contrast, heavy rainfall may wash away breeding sites, interrupt the development of mosquito eggs or larvae [21]. The seasonal pattern indicates that the peak of the dengue-endemic in Bangkok usually occurs in November during the study period, which is generally outside the rainy season.…”
Section: Discussionmentioning
confidence: 97%
“…Also, stagnant water and poor sanitary and hygiene practices may make suitable breeding sites for the mosquitoes. In contrast, heavy rainfall may wash away breeding sites, interrupt the development of mosquito eggs or larvae [21]. The seasonal pattern indicates that the peak of the dengue-endemic in Bangkok usually occurs in November during the study period, which is generally outside the rainy season.…”
Section: Discussionmentioning
confidence: 97%
“…Rainfall has been generally thought to be a positive predictor of dengue vector abundance as it provides essential mosquito habitats 11,14 . Recent studies, however, have demonstrated that excess rain may also flush away eggs, larvae or pupae of mosquitoes and remove mosquito breeding sites 15,16 , hence negatively effecting dengue incidence. Another study has found that dry seasons followed by a period of excess rainfall can lead to a high risk of dengue outbreaks, indicating that either positive or negative effects can occur, however, with different time lags 17 .…”
mentioning
confidence: 99%
“…Rainfall provides a water source that serves as a breeding site for female mosquitoes and an environment for immature larva/pupa, resulting in abundant mosquitoes and dengue outbreaks [11,12]. However, a large amount of rain may have a flushing effect, increasing the mortality rate of adult mosquitoes and larvae [13,14]. Temperature plays a major role in the development, survival, and feeding behavior of mosquitoes and encourages viral replication inside the vector [11].…”
mentioning
confidence: 99%